Mental Stress of Parents Having Thalassemic Children - Rayhan, Md Golam; Nurunnabi, Mohammad; Kabir, Shahnaz; Alam, Badrul (KYAMC Journal, 2022)
Background: Thalassaemia is an emerging global public health concern. It is considering as a rapidly growing major health burden for low- and middle income countries. The prevalence of thalassaemia is increasing in Bangladesh, indicates that thalassemia will be an emerging health burden for our country. Objective: To assess the level of mental stress among parents with a thalassemic child. Materials and Methods: A cross-sectional study was conducted among the 141 parents with a thalassemic child in the purposively selected two hospitals’ Dhaka Shishu Hospital and Bangladesh Thalassemia Hospital in Dhaka. ‘Parental stress scale’ (PSS) was used to measure the level of stress. Results: The mean age of the parents was 36.2±8.8 years and nearly two-thirds (63.8%) of them were aged below 40 years. Almost half of the participants (49.6%) and their spouses (59.6%) completed their education upto the higher secondary level. The mean monthly family income was 27,113.5±46,696.9 taka. More than half of the parent’s (53.2%) had low level of mental stress. The education, occupation, monthly family income, presence of >1 thalassaemic child in family, received blood from a voluntary blood donor, normal growth of thalassaemic child and history of thalassaemic child death were significantly associated with the level of mental stress by PSS scores of the parents (p<0.05). The level of stress was low among the parents, whose educational level was up to primary level (68.6%), occupation as a business (68.4%), monthly family income ≥50,001 taka (85.7%), presence of >1 beta thalassaemia major child (47.6%), received blood from a voluntary blood donor (50.0%), had a history of normal growth of thalassaemic child (60.4%) and had no history of thalassaemic child death (50.0%). Conclusion: Existence of the children with thalassemia in a family cause massive stress and anxiety for parents. Psychological supports for them are essential as a part of comprehensive medical care along with clinical management of the thalassemic child. The burden of disease can be reduced through effective preventive approaches, such as carrier screening, prenatal counseling and diagnosis. KYAMC Journal Vol. 13, No. 02, July 2022: 102-107